Designing English Education Game Application for Early Childhood - L. Albion; M. R. Kaira; Tatan Tawami; D. A. Fairuz; Hanhan Maulana (Universitas Pendidikan Indonesia (UPI), 2021)
This research aims to design a game app design that can help increase children's interest in learning English. The research method used descriptive qualitative by looking at early childhood learning during this pandemic, especially learning English, with additional data from literature studies. The system development method uses the waterfall method consisting of five stages: Requirement Analysis, Design, Implementation, Testing, Maintenance, and object approach method with tools such as use case, activity diagram, and interface design to produce an orderly system. The design of the game application is named GUTHEWORDS. It is expected to help increase children's interest in learning English to guess vocabulary such as animal names and numbers in English to help improve teaching success by making the teaching method fun and interesting for children. Through the implementation of learning through this game, it is expected to make it easier for children to learn to read, remember and hear some vocabulary in English well, also expected to explore the potential, creativity, and interest of children in learning English.